Effect of top-dressed monensin of beef cattle perfermance - ΚΑΤΣΑΟΥΝΗΣ Ν.; ΖΥΓΟΓΙΑΝΝΗΣ Δ.; ΚΥΡΙΑΚΗΣ Σ.; ΤΣΑΛΤΑΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In a 16 week experiment, Polish-Friesian bulls were hand fed a monensin mineral mixture top-dressed to the complete feed. Of the 44 bulls involved, 22 were given 125 mg monensin per head daily for the first month and 250 mg thereafter. The remaining bulls received the same mineral mixture without monensin. Bulls fed monensin gained 1,8% more than controls and improved their feed conversion ratio by 11,3%. The average daily feed intake was reduced by 8,9% in the monensin fed bulls as compared to controls.